Practical quantum key distribution - Ali, Sellami (IGI Global, 2012)
We have presented a method to estimate parameters of the decoy state protocol based on one decoy state protocol for both BB84 and SARG04. This method can give different lower bound of the fraction of single-photon counts (y1), the fraction of two-photon counts (y2), the upper bound QBER of single-photon pulses (e1), the upper bound QBER of two-photon pulses (e2), and the lower bound of key generation rate for both BB84 and SARG04. The effects of statistical fluctuations on some parameters of our QKD system have been presented. We have also performed the optimization on the choice of intensities and percentages of signal state and decoy states which give out the maximum distance and the optimization of the key generation rate. The numerical simulation has shown that the fiber based QKD and free space QKD systems using the proposed method for BB84 are able to achieve both a higher secret key rate and greater secure distance than that of SARG04. Also, it is shown that bidirectional ground to satellite and inter-satellite communications are possible with our protocol. The experiment of decoy state QKD has been demonstrated using ID-3000 commercial QKD system based on a standard ‘Plug & Play’ set-up. One decoy state QKD has been implemented for both BB84 and SARG04 over different transmission distance of standard telecom fiber.